Projections in string theory and boundary states for Gepner models - Fuchs, Jürgen; Schweigert, Christoph; Walcher, Johannes (Nuclear physics. B, Particle physics, 2000)
In string theory various projections have to be imposed to ensure supersymmetry. We study the consequences of these projections in the presence of world-sheet boundaries. A-type boundary conditions come in several classes; only boundary fields that do not change the class preserve supersymmetry. Our analysis takes in particular properly into account the resolution of fixed points under the projections. Thus, e.g., the compositeness of some previously considered boundary states of Gepner models follows from chiral properties of the projections. Our arguments are model independent; in particular, integrality of all annulus coefficients is ensured by model independent arguments.